VD_FINDINFO HC / 2014 / 721 vom 16. September 2014 - VD Tribunal cantonal (2014)
RÉPONSEACTION EN JUSTICE, DÉCISION D'IRRECEVABILITÉ | 132 al. 1 CPC (CH), 132 al. 2 CPC (CH), 132 CPC (CH), 221 al. 1 let. d CPC (CH), 221 al. 1 let. e CPC (CH), 221 CPC (CH), 222 al. 2 CPC (CH)